Anti-oxidative stress response in Drosophila melanogaster - The role of adipokinetic hormone and adenosine - Zemanová, Milada (Jihočeská univerzita, 2017)
In this thesis, the phenomena of the oxidative stress (OS) and anti oxidative stress responses in insects are described in a comprehensive review, and the outcomes of the experimental work are presented. The focus of the work was on defence reactions and their putative control by the adipokinetic hormone (AKH) and adenosine in the Drosophila melanogaster model. For this purpose, we studied the effect of the paraquat (oxidative stressor) treatment on adult flies and larvae carrying mutations in Akh (Akh1) and adenosine receptor (AdoR1) genes, and in both these genes together (Akh1 AdoR1 double mutant). The initial mortality tests revealed the double mutant Akh1 AdoR1 was more sensitive to OS than either of the single mutants. The AKH synthesis under the OS condition seems to be out of the gene expression control, since the increase of an AKH amount in CNS was not linked with the stimulation of Akh gene expression after a paraquat treatment. Further, the gene expression of the antioxidant enzyme glutathione S transferase D1 (GstD1) increased rapidly with OS, though the enzyme activity increased negligibly regardless of both the OS and mutations. Interestingly, the relative expression of GstD1 gene was minimal in the double Akh1 AdoR1 mutant; thus, it was concluded that both AKH and adenosine are employed in the GstD1 gene expression control. Similarly, AKH and adenosine seem to act in tandem in glutathione (GSH) regeneration, since the GSH level was significantly lower in all untreated deficient flies with the maximal effect in the Akh1 AdoR1 double mutant; accordingly, the reduction in the GSH level was enhanced by paraquat treatment. Altogether, the important roles of both AKH and adenosine in the anti oxidative stress response in D. melanogaster were demonstrated.
Anti-oxidative stress response in Drosophila melanogaster - The role of adipokinetic hormone and adenosine
Keywords: Oxidative stress; adipokinetic hormone; adenosine; Drosophila melanogaster; paraquat; anti-oxidative response; regulation; Oxidative stress; adipokinetic hormone; adenosine; Drosophila melanogaster; paraquat; anti-oxidative response; regulation